INTEGRATED APPLICATION OF OPTICAL DIAGNOSTIC METHODS IN ULCERATIVE COLITIS - E. V. Velikanov; S. G. Tereschenko; V. I. Shumsky; L. E. Gaganov; L. G. Lapaeva; N. V. Nikitina; I. E. Svinzov (Неотложная медицинская помощь)
Abstract. Our results suggest that the combined use of optical coherent tomography (OCT) and fluorescence diagnosis helps to refine the nature and boundaries of the pathological process in the tissue of the colon in ulcerative colitis. Studies have shown that an integrated optical diagnostics allows us to differentiate lesions respectively to histology and to decide on the need for biopsy and venue. This method is most appropriate in cases difficult for diagnosis.